Role of the sodium-glucose linked transporte 2 (SGLT2) inhibitor in the treatment of Diabetes Mellitus type 2 - Gamarra-González, Dante Américo (2020)
A review of renal physiopathology of diabetes mellitus type 2 (DM2) is performed. The paradigmatic focusing of the DM2 treatment by means only on the glycemic control is analyzed. A review of mechanism of action of the so called sodium-dependent glucose cotransporters inhibitors type 2 (SGLT2) is done as well as its indications, cardiovascular safety, pleiotrophic effects, potential side effects and their role in dismissing the severity and mortality due cardiovascular and renal complications. The three main STLT2 inhibitors (dapagliflozin, canagliflozin and empagliflozin) have demonstrated efficacy in the treatment ofDM2 both as mono therapy as well as in combination with insulin and/or oral hypoglycemic agents. They produce a significant weight loss, beneficial effects on blood pressure and changes in lipid profile.